2021
DOI: 10.33073/pjm-2021-001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Ambient Temperatures on Caecal Microbial Composition in Broilers

Abstract: Short-term or acute temperature stress affect the immune responses and alters the gut microbiota of broilers, but the influences of long-term temperature stress on stress biomarkers and the intestinal microbiota remains largely unknown. Therefore, we examined the effect of three long-term ambient temperatures (high (HC), medium (MC), and low (LC) temperature groups) on the gene expression of broilers’ heat shock proteins (Hsps) and inflammation – related genes, as well as the caecal microbial composition. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 50 publications
(37 reference statements)
0
5
0
Order By: Relevance
“…However, the study did not elucidate a detailed mechanism [89]. An additional study found that the abundance of Phascolarctobacterium in the gut increases when chickens are exposed to high temperatures for extended periods, and this exposure also results in elevated levels of heat shock proteins and related inflammatory gene expression [90]. Heat stress altered the structure and function of enzymes in the chicken body, reduced the pH of the blood, and caused metabolic acidosis.…”
Section: Discussionmentioning
confidence: 93%
“…However, the study did not elucidate a detailed mechanism [89]. An additional study found that the abundance of Phascolarctobacterium in the gut increases when chickens are exposed to high temperatures for extended periods, and this exposure also results in elevated levels of heat shock proteins and related inflammatory gene expression [90]. Heat stress altered the structure and function of enzymes in the chicken body, reduced the pH of the blood, and caused metabolic acidosis.…”
Section: Discussionmentioning
confidence: 93%
“…Tian et al (2020) reported a decrease in the abundance of Shaoxing duck Enterococci after 15 days of high temperature exposure, which was different from the results of the present experiment. Enterococcus is not only a major component of the chicken intestinal ora, but it is also a highly pathogenic conditional pathogen (Yang et al 2021). Enterococcus causes arthritis, spondylitis and reduced production performance in broilers by destroying eukaryotic DNA in intestinal epithelial cells (Kense et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…All cats were stray at study initiation; thus, their exact date of birth was unknown and slight differences in the enrollment age might have influenced the microbiota composition. Differences in ambient could have also interfered with our results [ 102 ]. Some cats were malnourished, and malnourishment has been associated with a persistently immature microbiome in children [ 103 ].…”
Section: Discussionmentioning
confidence: 99%